Prospects for distributed self-consumption generation in urban circuits with the use of photovoltaic systems - Diego Cordova; Secundino Marrero; Carlos Quinatoa; Manuel Leon (Frontiers in Energy Research)
Electric distribution systems currently present a marked interest in solving problems related to technical losses, overloading of lines and being able to assimilate the increase in energy demand. Therefore, the objective of this research was to analyze the behavior of a network in the presence of distributed generation, taking into account the efficiency in operations, stability and compliance with the established technical standards. The problem studied is related to the inefficiency present in some systems to incorporate distributed generation and cover the demand in certain sectors, in the presence of overloads, increased costs and reliability losses. The methodology used in the research considers power flow, equivalent circuit modeling and computational simulations to evaluate the behavior of the network in different scenarios. The results show a favorable balance of loads at the nodes, thus achieving a more efficient use of existing assets and enhancing the planning of transmission routes. This research demonstrates the importance of incorporating DG and its technical feasibility in 75% of all nodes in the case studied, thus promoting energy sustainability, emphasizing the importance of implementing these strategies to ensure a reliable, efficient and scalable supply with an important contribution to the sustainable development of electricity systems in contexts of high demand and limited resources in distribution networks.